Perbandingan Implementasi Sistem Bunga dan Sistem Bagi Hasil (Revenue Sharing) - Oktafiani, Nurlatifah Umi; Itang; Dede Sudirja (Masyarakat Ekonomi Syariah Bogor, 2024)
This research discusses the use of capital production factors in an Islamic economic perspective with a comparative focus between the profit sharing system and the interest system. In Islamic economics, production activities are based on the motive and spirit of benefit, justice and blessing accompanied by limitations on Islamic economic principles. This research uses a descriptive qualitative method with a literature approach to find and explain choices of capital sources that are effective, efficient, and in accordance with the Islamic economic perspective in managing production costs and producer behavior in the context of Islamic economics. The research results show that the use of a profit sharing system is more effective in reducing total production costs compared to the interest system. Interest expenses in the interest system tend to increase total production costs which have an impact on reducing profits. The profit sharing system allows for a fair distribution of profits and losses between capital owners and capital managers, reduces the burden of production costs, and brings blessings in wealth management. Therefore, producers who adhere to Islamic economic principles tend to choose a profit sharing system rather than an interest system. This is because the profit sharing system is fairer and more effective in reducing production costs and is in line with Islamic economic values.